Kontribusi Body Comparison Dengan Artis K-Pop Perempuan Terhadap Body Dissatisfaction (Studi pada Remaja Perempuan Indonesia Fans K-Pop) - Lita Dwiputeri; Venie Viktoria Rondang Maulina (Universitas Katolik Indonesia Atma Jaya, 2015)
K-pop is a popular music genre from South Korea. K-pop female actresses or singers have an ideal body, which are desired by female K-pop fans. K-pop female actresess‟ ideal body can be regarded as a standard by female adolescent K-pop fans for body comparison, which can be defined as a comparison process with other‟s body. Female adolescent K-pop fans who do body comparison with K-pop female artist can have body dissatisfaction, which is defined as unfavorable or disparaging opinion of their own body components. Based on that phenomenon, this research investigates the contribution of body comparison with K-pop female artist to Indonesian female adolescent K-pop fans‟ body dissatisfaction. This research is quantitative research. Data were collected through giving questionnaires to 165 female adolescent K-pop fans in Indonesia. These questionnaires consist of the Body Satisfaction Scale, which was constructed by Slade, Dewey, Newton, Brodie, and Kiemle, for measuring body dissatisfaction. These questionnaires also consist of the Body Comparison with K-pop Female Artist Scale, which was adapted from the Body Comparison Scale by Thompson and Fisher. Data collected were analyzed using simple regression analysis. The result shows that body comparison with K-pop female artist contributes significantly to Indonesian female adolescent K-pop fans‟ body dissatisfaction. K-pop is a popular music genre from South Korea. K-pop female actresses or singers have an ideal body, which are desired by female K-pop fans. K-pop female actresess‟ ideal body can be regarded as a standard by female adolescent K-pop fans for body comparison, which can be defined as a comparison process with other‟s body. Female adolescent K-pop fans who do body comparison with K-pop female artist can have body dissatisfaction, which is defined as unfavorable or disparaging opinion of their own body components. Based on that phenomenon, this research investigates the contribution of body comparison with K-pop female artist to Indonesian female adolescent K-pop fans‟ body dissatisfaction. This research is quantitative research. Data were collected through giving questionnaires to 165 female adolescent K-pop fans in Indonesia. These questionnaires consist of the Body Satisfaction Scale, which was constructed by Slade, Dewey, Newton, Brodie, and Kiemle, for measuring body dissatisfaction. These questionnaires also consist of the Body Comparison with K-pop Female Artist Scale, which was adapted from the Body Comparison Scale by Thompson and Fisher. Data collected were analyzed using simple regression analysis. The result shows that body comparison with K-pop female artist contributes significantly to Indonesian female adolescent K-pop fans‟ body dissatisfaction.